A Glycoengineered Interferon-β Mutein (R27T) Generates Prolonged Signaling by an Altered Receptor-Binding Kinetics - Lee, Saehyung; Son, Woo Sung; Yang, Ho Bin; Rajasekaran, Nirmal; Kim, Sung-Su; Hong, Sungyoul; Choi, Joon-Seok; Choi, Jun Young; Song, Kyoung; Shin, Young Kee (Frontiers in Pharmacology, 2019)
The glycoengineering approach is used to improve biophysical properties of protein-based drugs, but its direct impact on binding affinity and kinetic properties for the glycoengineered protein and its binding partner interaction is unclear. Type I interferon (IFN) receptors, composed of IFNAR1 and IFNAR2, have different binding strengths, and sequentially bind to IFN in the dominant direction, leading to activation of signals and induces a variety of biological effects. Here, we evaluated receptor-binding kinetics for each state of binary and ternary complex formation between recombinant human IFN-β-1a and the glycoengineered IFN-β mutein (R27T) using the heterodimeric Fc-fusion technology, and compared biological responses between them. Our results have provided evidence that the additional glycan of R27T, located at the binding interface of IFNAR2, destabilizes the interaction with IFNAR2 via steric hindrance, and simultaneously enhances the interaction with IFNAR1 by restricting the conformational freedom of R27T. Consequentially, altered receptor-binding kinetics of R27T in the ternary complex formation led to a substantial increase in strength and duration of biological responses such as prolonged signal activation and gene expression, contributing to enhanced anti-proliferative activity. In conclusion, our findings reveal N-glycan at residue 25 of R27T is a crucial regulator of receptor-binding kinetics that changes biological activities such as long-lasting activation. Thus, we believe that R27T may be clinically beneficial for patients with multiple sclerosis.